Ten years of maternity claims: an analysis of the NHS Litigation Authority data – key findings. (January 2013) - Anderson, Annette
Maternity claims, as a group, are the most expensive clinical negligence claims reported to the NHS Litigation Authority (NHSLA) and the second highest by volume. As a consequence, the NHS LA launched a project Ten Years of Maternity Claims – An Analysis of NHS Litigation Authority Data reviewing maternity claims with an incident date between 1 April 2000 and 31 March 2010. This analysis was initiated to enable key trends to be identified, and to share the learning widely within the National Health Service (NHS) with a long-term goal of reducing harm occurring to women and babies accessing maternity care. During this period there were 5087 claims with a total value of £3.1 billion. Between the years 2000 and 2009 there were 5.5 million births in England. In all, 0.1% of births were subject to a clinical negligence claim. In other words, the vast majority of births do not result in a clinical negligence claim, which supports the view that having a baby within the NHS is very safe. As part of the project, primary and secondary level studies were undertaken. The former analysed the occurrence of types of maternity claim and the financial costs associated with them. The most frequent categories identified related to the management of labour, which involves fetal heart rate monitoring (14.05%), Caesarean section (13.24%) and cerebral palsy (10.65%). The secondary level study reviewed four categories of maternity claims which were chosen subjectively from discussions with stakeholders. The categories identified were – antenatal ultrasound investigations, cardiotocograph interpretation, perineal trauma and uterine rupture. By undertaking additional in depth analysis the objective was to identify factors from which risk management recommendations could be formulated to facilitate learning from claims, with the aim of reducing cases of actual harm to mothers and babies. This article highlights the key findings from the study and suggests recommendations for ongoing learning within maternity services.